The Single-Buyer Model : A Dangerous Path toward Competitive Electricity Markets - Lovei, Laszlo (World Bank, Washington, DC, 2012)
Many Asian, African and Eastern European countries freeing up their electricity markets are preserving an artificial monopoly over the wholesale trading of electricity even after the vertically integrated national power company is unbundled. Evidence so far suggests that this single buyer model has major disadvantages in developing countries: it invites corruption, weakens payment discipline, and imposes contingent liabilities on the government. These disadvantages in most cases overshadow the higher short-term costs of a bilateral contracts model where generators contract with customers.